Leksem Penanda Plagiat dalam Portal Berita Koreaboo: Kajian Semantik - Dhiya'un Nabila Hasya; Elvi Citraresmana; Hera Meganonova Lyra (Lingua Susastra, 2026)
This study analyzes the lexemes used in plagiarism-related reporting on the Koreaboo news portal through a lexical-semantic approach. The data consist of 141 English-language articles published between April 2023 and April 2024. The study employs a qualitative descriptive method using content analysis. The findings show five lexemes used to frame plagiarism-related issues: plagiarize, copy, steal, borrow, and mimic. Among them, plagiarize denotes plagiarism lexically, while copy undergoes semantic narrowing, steal shifts metaphorically from physical theft to idea theft, borrow shows semantic broadening, and mimic refers to excessive imitation with negative evaluation. These findings indicate that Koreaboo constructs plagiarism meanings progressively through lexical choice and discourse context. Theoretically, the study supports the view that lexical meaning is strongly shaped by context. Practically, it shows that news language is not neutral, as it also shapes readers’ judgments about plagiarism issues.